Reducing Maternal Mortality From Preeclampsia and Eclampsia in Low-Resource Countries: What Should Work?. Issue 1 (March 2016) - Goldenberg, R.L.; Jones, B.; Griffin, J.B.; Rouse, D.J.; Kamath-Rayne, B.D.; Trivedi, N.; Mcclure, E.M.
Abstract : ( Acta Obstet Gynecol Scand. 2015;94:148–155) Preeclampsia/eclampsia may account for 15% of maternal mortality, as well as roughly 25% of fetal mortality. The risk of eclampsia was greatly reduced in wealthier countries during the 20th century.